COMMUNICATING FOR SUCCESS - Brindusa Maria Popa (Journal of Defense Resources Management, 2016)
Organizational communication, both internal and external, affects organizational efficiency and effectiveness and consequently, the objectives of the organization. Communication is one the elements of the organizational life which is taken for granted and most of the times overlooked. It is pervasive and inherent in all activities thus, it cannot be analyzed in isolation, but in an organizational context. A well structured communication system will impact the performance of the organization through the quantity, but mostly the quality of the information it transports. Information should be clear, concise, specific, open, multi-directional.